Serum Vitamin D is Di erentially Associated with Socioemotional Adjustment in Early School-Aged Ugandan Children According to Perinatal HIV Status and In Utero/Peripartum Antiretroviral Exposure History - Yakah, William; Fenton, Jenifer I.; Sikorskii, Alla; Zalwango, Sarah K.; Tuke, Robert; Musoke, Philippa; Boivin, Michael J.; Giordani, Bruno; Ezeamama, Amara E. (Nutrients, 2019)
An impact of vitamin D in neurocognitive function has been theorized but it remains unknown whether vitamin-D insufficiency (VDI) is associated with worse socio-emotional adjustment (SEA) in vulnerable early school-aged children. This study examines the thesis that deficits in SEA are related to VDI using longitudinal data from 254 children that are perinatally HIV-infected (PHIV), exposed-uninfected (HEU), or unexposed-uninfected (HUU). In utero/peripartum antiretroviral (IPA) exposure was established per medical record documentation of biological mother’s ART regimen in pregnancy. Four caregiver-reported age- and sex-standardized measures of SEA were obtained at months 0, 6, and 12 for dependent children aged 6–10 years: externalizing problems (EPC), internalizing problems (IPC), behavioral symptoms index (BSI), and adaptive skills index (ASI). VDI was highly prevalent (74%, n = 188), and its association with change in SEA measures over 12 months varied by HIV-status (VDI*HIV, all p-values < 0.03). There was further variation in relationship of vitamin-D to SEA by IPA among PHIV (for ASI, BSI, and EPC, vitamin-D*IPA, p-value ≤ 0.01) and HEU (for BSI and EPC, vitamin-D*IPA, p-value ≤ 0.04). Among HUU, BSI (β = −0.32, 95% CI: −0.50, −0.13), IPC (β = −0.28, 95% CI: −0.47, −0.09), and EPC (β = −0.20, 95% CI: −0.37, −0.02) all declined moderately per quartile increment in VD. Among PHIV, on the one hand higher vitamin D predicted ASI gains (moderate vs. low VD, β = 0.52, p = 0.002), but this protective association was absent for BSI, EPC, and IPC (β = 0.36–0.77, p < 0.05). In absence of IPA-exposure, increasing vitamin-D predicted declines in BSI and EPC (moderate vs. low Vitamin D, β = −0.56 to −0.71, p ≤ 0.02) among HEU. However, given IPA exposure among HEU, higher VDI predicted moderate elevation in BSI (β = 0.39, 95% CI: 0.00, 0.78) and IPC (β = 0.48, 95% CI: 0.05, 0.92). Interaction between VD and IPA exposure for SEA outcomes among HEU and PHIV children warrants further investigation. The vitamin-D associated SEA improvement among HUU and HEU without IPA exposure suggests vitamin-D supplementation may remediate behavioral and adaptive deficits in this groups. View Full-Text
Keywords: vitamin D; antiretroviral therapy; perinatal HIV infection; Uganda; cognition; socioemotional adjustment